Development of PVA-Chitosan/PANi hydrogels for environmental applications - Zulkifli, Ahmad Akid; Sa’adon, Muhammad Hazwan; Serati, Flora; Mohd Zaki, Syazwani (Persatuan Saintis Muslim Malaysia (PERINTIS), 2023)
This paper focused on a new, alluring, and environmentally friendly technique for possible seawater desalination and water purification: solar-driven steam generation or solar vapor generation (SVG). SVG has two basic components consisting of a substrate for water transportation and a light absorber for converting light energy to heat energy. Hydrogel is a physically or chemically crosslinked polymer chain network that has the potential to be used for harvesting fresh water owing to its threedimensional networking structure hydrogel. A polymer chain of crosslinked structures has a fixed shape and can swell by absorbing water or organic solvent. The mechanism of harvesting fresh water with hydrogel involves solar energy that vaporizes impurities from water and results in freshwater. This is important in combating the ongoing water scarcity problems, especially in remote areas with limited access to clean water. Overall, this experiment aims to investigate on PVA-Chitosan/PANI hydrogels with different amounts of glutaraldehyde (GA) content. From the swelling behavior experiment, hydrogel with 14.5 µl GA content showed the maximum swelling ratio at pH 10 with Qgel = 1.68 at pH 10 and at pH 4 with Qgel = 1.54. The water uptake of such hydrogels depends on environmental conditions such as pH, ionic strength, temperature, and electrical or magnetic field. Furthermore, the higher content of GA increased the number of pores in the hydrogel network structure, which enabled it to transport water more easily for real-life applications.